Angioinvasion as a factor for predicting aggressive outcome in primary thyroid angiosarcoma: three case reports and literature review - Nechifor-Boilă, Adela; Decaussin-Petrucci, Myriam; Varga-Ilyés, Agota; Chinezu, Laura; Caraşca, Cosmin; Borda, Angela (Polish Journal of Pathology, 2018)
We report three primary thyroid angiosarcoma (PTA) cases revealing distinctive morphological features. A systematic literature review completed our analysis to evaluate the most important morphological factors for predicting prognosis in PTAs. Three rare PTA cases were analysed. In addition, we identified 46 previously reported PTAs with available follow-up data to compare morphological features related to prognosis between patients with a favourable versus aggressive outcome. The three PTAs displayed considerable architectural heterogeneity: case 1 presented a well circumscribed tumour, extensively necrotic, with only a few highly pleomorphic vascular proliferation; cases 2 and 3 both exhibited plump epithelioid cells forming rudimentary vascular spaces or solid sheets. Case 3 also presented angioinvasion. Cases 1 and 2 were alive and disease-free at 40 and 73 months following diagnosis, respectively, whereas case 3 died within 14 months. Other significant prognostic factors were highlighted by our review and literature data analysis: increased tumour size (p = 0.042), extrathyroidal extension (p = 0.009), and distant metastases at diagnosis (p = 0.001). Although regarded as highly aggressive, PTA can also be characterised by an unusual favourable outcome. For the first time we highlight the importance of reporting angioinvasion, in cases of PTA, as a possible adverse prognostic factor.